Perspective: Utilizing High Amylose Wheat Flour to Increase Dietary Fiber Intake of Children and Adolescents: A Health by Stealth Approach - Harris, Kathryn; Overcash, Francine; Belobrajdic, Damien; Slavin, Joanne (Frontiers in Public Health, 2022)
Children and adolescents have consistently failed to meet recommended levels of dietary fiber consumption, thus making fiber a nutrient of concern. The importance of adequate dietary fiber intake to attain a healthy diet necessitates the identification of fiber rich and readily consumed food sources by youth. Grain-based foods derived from whole grains represent a strategic initiative to increase dietary fiber consumption and is consistent with the American diet pattern. Increased intake of foods made from whole grains have been positively associated with improved health outcomes but are also less preferred among youth compared to refined grain products, which make up the majority of their carbohydrate intake. Advances in the commercialization and availability of high amylose wheat flour, a source of resistant starch fiber, provides an opportunity to remedy the suggested acceptability issues of whole grain products indicative of sensory factors, without compromising the amount fiber ingested. Resistant starch fiber consumption has been associated with health benefits including improved blood sugar management, improved markers of digestive and gut health, increased satiety, and a reduced inflammatory response among adults. The limited studies that indicate fiber’s direct benefit among youth are largely observational, thereby necessitating the need for more controlled trials for these age groups. Replacing traditional refined wheat flour with refined high amylose wheat flour has the unique ability to increase dietary fiber consumption without compromising desired sensory and finished product characteristics and thus can help increase dietary fiber consumption in children and adolescents who struggle to meet adequate intakes of fiber.